2004
DOI: 10.1016/j.jhsb.2003.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of mRNA Levels for Matrix Molecules and TGF-β1 in Rabbit Flexor and Peroneus Tendons Reveals Regional Differences in Steady-State Expression

Abstract: This study analysed the differences on a molecular level between two segments of the deep flexor tendon, and compared the intrasynovial flexor tendon with the tendon sheath and the extrasynovial peroneus tendon in a rabbit model. The TRIspin method of RNA extraction was combined with the reverse transcription polymerase chain reaction to assess mRNA levels in the tissue segments. Significant differences were detected for all genes studied. mRNA levels for aggrecan, biglycan and collagen III were significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
(36 reference statements)
1
14
0
Order By: Relevance
“…However, the distinct molecular signatures of adjacent regions that had similar basal gene expression but were exposed to different stresses in transected tendons (e.g., regions 3 and 4), strongly implicated regional biomechanical forces in primarily regulating the differentially affected genes in these regions, such as lumican, aggrecan, and ADAMTS. Consistent with the findings of a previous study (26), our results showed that the phenotype of tenocytes in tendon closer to the bone attachment differed from that in the tensile regions. Consequently, the cells may not respond in a similar manner either to cytokine or growth factor stimulation or to altered mechanical signals (stress deprivation/ overstress).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the distinct molecular signatures of adjacent regions that had similar basal gene expression but were exposed to different stresses in transected tendons (e.g., regions 3 and 4), strongly implicated regional biomechanical forces in primarily regulating the differentially affected genes in these regions, such as lumican, aggrecan, and ADAMTS. Consistent with the findings of a previous study (26), our results showed that the phenotype of tenocytes in tendon closer to the bone attachment differed from that in the tensile regions. Consequently, the cells may not respond in a similar manner either to cytokine or growth factor stimulation or to altered mechanical signals (stress deprivation/ overstress).…”
Section: Discussionsupporting
confidence: 92%
“…Increased aggrecan mRNA and/or protein has been documented in normal tendons in regions of compression and at sites of bone attachment (26,(29)(30)(31)(32). In these fibrocartilaginous regions of normal tendon, the increase in aggrecan is accompanied by elevated levels of biglycan and type II and type IX collagens.…”
Section: Discussionmentioning
confidence: 99%
“…After opening the flexor tendon sheaths with a longitudinal incision between the first and second pulleys, the superficial flexor tendons were resected in the area of the tendon sheath corresponding to zone II in humans. The deep flexor tendons were then divided completely with a sharp cut through the intermediate segment proximal to the distal joint (Berglund et al 2004). A modified Kessler suture (5-0 Prolene, Ethicons, Johnson and Johnson, Sollentuna, Sweden) was used as the core suture of the tendon, and a running suture (7-0 PDS, Ehicons, Johnson and Johnson, Sollentuna, Sweden) as the circumferential suture of the tendon repair.…”
Section: Animal Model Of Flexor Tendon Injurymentioning
confidence: 99%
“…Polymerase chain-reaction analysis was subsequently performed with rabbit-specific primers for molecules relevant to synthesis and degradation of tendon matrix (see Appendix), as described previously [21][22][23] . Absence of DNA contamination was confirmed with a negative control of non-reverse-transcribed total RNA.…”
Section: Tendon Water Contentmentioning
confidence: 99%